2007
DOI: 10.1902/jop.2007.060218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Curet and Paper Point Sampling of Subgingival Bacteria as Analyzed by Real‐Time Polymerase Chain Reaction

Abstract: Overall, there was a relatively good agreement for the results of paper point and curet sampling. Thus, both techniques seem to be suitable for microbiological diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 17 publications
2
61
1
Order By: Relevance
“…A possible explanation for these findings may be the absorbent properties of the PP making them more prone to absorb crevicular fluid, desquamated cells, lysed leukocytes and human DNA debris. Outcomes of the present study are in line with those reported by Jervøe-Storm et al (2007), who evaluated by qPCR the amount of bacterial DNA in samples collected by PP and curettes from sites with PD N 5 mm in ChP subjects. The authors showed that curettes recovered significantly more total bacteria DNA than PP.…”
supporting
confidence: 89%
“…A possible explanation for these findings may be the absorbent properties of the PP making them more prone to absorb crevicular fluid, desquamated cells, lysed leukocytes and human DNA debris. Outcomes of the present study are in line with those reported by Jervøe-Storm et al (2007), who evaluated by qPCR the amount of bacterial DNA in samples collected by PP and curettes from sites with PD N 5 mm in ChP subjects. The authors showed that curettes recovered significantly more total bacteria DNA than PP.…”
supporting
confidence: 89%
“…However, the present findings contradict those of studies reporting a positive correlation of number of P. gingivalis with PPD and PAL (39,40). There are a number of possible explanations for this inconsistency, including differences in disease status at the sampled site and the method used to detect and estimate the copy numbers of pathogens present (41). Loomer reported that analysis of the overall oral microbiota profile of a patient is more representative when a greater number of sites is sampled (42).…”
Section: Discussioncontrasting
confidence: 97%
“…In comparison to paper points, curettes collect plaque from the entire pocket lining. [17] Polymerase chain reaction (PCR) based methods are more specific and sensitive as they are based on detection of gene specific DNA sequences. Hence, it represents a valuable method to determine the viral load in diseased and healthy sites.…”
Section: International Journal Of Dental Researchmentioning
confidence: 99%